2016
DOI: 10.5897/ajb2015.15107
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of sweet potato [Ipomoea batatas (L.) Lam] value chain upgrading as revealed by physico-chemical composition of ten elites landraces of Benin

Abstract: Sweet potato is one of the most important food security promoted root crops in the world, especially in sub-Saharan Africa. Unfortunately, the crop is still neglected and underutilized in Benin Republic. To establish baseline data for its better utilization for upgrading its value chain, 10 selected local varieties (01 cream, 02 white, 03 yellow, and 04 orange flesh-colored) were compared for their macro-nutritional composition assessed using standard Association of Official Analytical Chemists (AOAC) procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
2
21
3
2
Order By: Relevance
“…This research revealed that L* value decreased with increasing sweet potato proportion, which may be attributed to the deep color of the sweet potato. Previous research indicated some varieties of sweet potatoes were rich in different colored pigments, such as β-carotene, anthocyanin, and phenolic compounds, are responsible for different colors in sweet potatoes [24]. These different pigments were responsible for different colors in food.…”
Section: Color Evaluation Of Steamed Rice Bowl Cakementioning
confidence: 99%
“…This research revealed that L* value decreased with increasing sweet potato proportion, which may be attributed to the deep color of the sweet potato. Previous research indicated some varieties of sweet potatoes were rich in different colored pigments, such as β-carotene, anthocyanin, and phenolic compounds, are responsible for different colors in sweet potatoes [24]. These different pigments were responsible for different colors in food.…”
Section: Color Evaluation Of Steamed Rice Bowl Cakementioning
confidence: 99%
“…It is increasingly produced in Benin, especially in the south of the country by small producers as a food during the lean season because of its ability to adapt to difficult conditions and its nutritional importance (Adégbloba, 2003;Sanoussi et al, 2013). Previous work on the species in Benin has shown the existence of a diversity of sweet potato landraces, some of which are increasingly neglected because of the many constraints that hinder production and whose conservation becomes a priority (Doussoh et al, 2016;Paraïso et al, 2013;Sanoussi et al, 2016). In vitro culture techniques are an alternative that is widely used for regeneration and transformation of sweet potato plants (Onwubiko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato (Ipomoea batatas (Lam)) is a dicotyledonous plant from the family Convolvulaceae that grows in tropical and subtropical areas and even in some temperate zones of the developing world [1]. It is a starchy, sweet tasting, tuberous root vegetable with smooth skin and comes in different coloursyellow, purple, orange and beige [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato is also an excellent source of vitamin A (14187 IU/100 g) and it is highly nutritious in terms of vitamin C (2.4 mg/100 g), calcium (30 mg/100 g) and iron which is required for adequate energy (0.61 mg/100 g) and magnesium (25 mg/100 g) [6,7]. Despite its high carbohydrate content, sweet potato has a low glycemic index due to low digestibility of the starch making it suitable for diabetic or overweighed people [8,9,10,11,1]. The root has higher protein content than other roots and tubers, such as cassava and yams [12].…”
Section: Introductionmentioning
confidence: 99%